Combat with Piracy and International Legal Responsibility - E. S. Anyanova (Московский журнал международного права, 2016)
Significant damage is caused to the world economy by piracy. And the critical “piracy situation” in the Gulf of Guinea in this relation is the clearest example. The successful solution of the long piracy crisis in the region of Somalia (in 2015 no piracy attacks was registered in the region, in 2016 – 1) is based on the joined efforts of the world community. Today in the area of maritime security here adequate (though great) efforts are enough on the national and regional/interregional levels.In the paper the general characteristics of piracy are analyzed, conclusions are made about the character of the existing international legal regulation in the fight with this crime, its influence on the global economics and interrelation on the samples of insurance, cost of maritime transport.